Hexafluoroisopropanol decreases liver ischemia-reperfusion injury by downregulation of high mobility group box‐1 protein - Agustin Vintimilla Moscoso; Estela Regina Ramos Figueira; Joel Avancini Rocha‐Filho; Martin Urner; Cinthia Lanchotte; Jose Jukemura; Jorge Luiz Saraiva Ximenes; Sergio Carlos Nahas; Luiz Augusto Carneiro D'Albuquerque; Flavio Henrique Ferreira Galvao (Wiley, 2022)
Abstract Liver ischemia-reperfusion (IR) injury is associated with poor outcome after liver transplantation and liver resections. Hexafluoroisopropanol (HFIP) is a tri‐fluorinated metabolites of volatile anesthetics and has modulatory effects on inflammation that have been observed mainly in cell culture experiments. In this survey, we investigated the effects of HFIP in a rat model of normothermic hepatic ischemia-reperfusion injury. Twenty‐four male Wistar rats were randomized into three groups: (1) control in which animals were submitted to 30 min of partial liver ischemia with resection of non‐ischemic liver lobes immediate after reperfusion, (2) pre‐ischemia (PI) group in which animals received intravenous HFIP (67 mg/kg) 5 min before liver ischemia, and (3) pre‐reperfusion (PR) group in which animals received intravenous HFIP (67 mg/kg) 5 min before reperfusion. Four hours after reperfusion, all animals were euthanized for sample collection. Aspartate and alanine transaminases, glucose, and high mobility group box‐1 (HMGB‐1) protein concentrations showed a significant decreased, and malondialdehyde was increased in the PR group compared with control and PI groups. Interleukin 6 (IL‐6) was increased in the PI group compared with control and PR groups. IL‐10 and ‐12 were increased in the PR and PI groups, respectively, when compared with the control group. Glucose decreased in the PR when compared with the control group. Post‐conditioning with HFIP led to a decrease in hepatocellular injury and was associated with a downregulation of HMGB‐1. The HFIP resulted in a better control of inflammatory response to ischemia-reperfusion even without causing a reduction in oxidative stress.